Volume of tourism traffic in a period of declining demand in Republic of Croatia and competing countries - Devčić, Kristina; Tonković Pražić, Ivana (Oeconomica Jadertina, 2023)
The emergence of the COVID-19 pandemic brought issues that tourism sectors and national economies were not faced with under normal conditions to the fore. In the newly created situation, due to restrictions in the movement of people, domestic guests have become the carriers of tourist traffic in all tourist markets, and only about 10% of the total number of tourists in the Republic of Croatia are domestic guests. However, unlike most competing countries, during the period of reduced demand, the Croatian tourism sector showed resilience due to the proximity of large European markets from which Croatia is easily and quickly accessible by car, such as Italy or Germany. This paper analyzes the dynamics of tourist overnight stays in the Republic of Croatia and in its competing countries (Spain, Greece and Portugal), in the period from 2018 to 2021. The analysis of trends in the volume of tourist traffic and the reaction and resilience of the tourism sectors of the aforementioned countries to changes caused by the emergence of the COVID-19 pandemic is the main subject of this research with the aim of preparing the tourism sector, that is, the national economy for similar global challenges in the future. A comparative analysis of tourist traffic before, during and after the period of reduced demand, between Croatia and selected competing countries, showed how the tourism sector reacted during the period of reduced demand. Future research should seek to answer how to strategically develop the tourism sector in order to build resilience to such challenges, and how to create preconditions for increasing the share of domestic guests in the structure of tourists visiting Croatia, to develop types of tourism that have proven to be more resilient during the pandemic (continental nature based tourism and cultural and gastronomy tourism), develop infrastructure capacities for individual, family and elite tourism, not mass tourism. At the level of national economies, it is necessary to find ways to limit or reduce the share of volatile, tertiary activities, which are the first to react negatively in crisis situations.